2015
DOI: 10.1039/c4ra12859a
|View full text |Cite
|
Sign up to set email alerts
|

[2.2.2]Paracyclophane, preference for η6 or η18 coordination mode including Ag(i) and Sn(ii): a survey into the cation–π interaction nature through relativistic DFT calculations

Abstract: [2.2.2]Paracyclophane is a versatile π-cryptating structure, which can exhibit η2:η2:η2 and η6:η6:η6 coordination with metal ions, involving two or six carbon atoms in each aromatic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
5
22
0
Order By: Relevance
“…These findings are directly related with our previously reported results for [2.2.2]paracyclophane . For a cation with electronic configuration 5s 0 5p 0 , the charge donation was found to be more effective in η 2 :η 2 :η 2 ‐[2.2.2]pCp → 5s 0 scheme, which has the interaction happening in a similar way to our η 1 :η 1 :η 1 cases in 1, and the η 1 :η 1 in 2.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are directly related with our previously reported results for [2.2.2]paracyclophane . For a cation with electronic configuration 5s 0 5p 0 , the charge donation was found to be more effective in η 2 :η 2 :η 2 ‐[2.2.2]pCp → 5s 0 scheme, which has the interaction happening in a similar way to our η 1 :η 1 :η 1 cases in 1, and the η 1 :η 1 in 2.…”
Section: Resultssupporting
confidence: 90%
“…The calculated cavity diameter for the isolated nanobelt 1 is 5.696 Å, while 5.676 Å is observed by single crystal X‐ray data . The inclusion of the Ag + and Cd 2+ cations into the cavity leads to slight increase in the cavity diameter, in agreement with the rigidity expected for the all‐sp 2 carbon backbone, whereas for the related [2.2.2]paracyclophane, an opening of the above face is accounted . Such finding is also supported by the small values of preparation energies, Δ E prep , obtained from EDA‐NOCV analysis, as discussed in the next section.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, such host for cations exhibits two well‐defined coordination modes toward ns and ( n ‐1) p elements, given as described for Ag + and Sn 2+ , respectively, involving a η 2 : η 2 : η 2 for the former, and η 6 : η 6 : η 6 for the latter. These different coordination behaviors were studied by relativistic DFT methods and it was found that the 5 seconds‐Ag shell is close in energy to the frontier orbitals of paracyclophane, resulting in the formation of a bonding scheme with the symmetric combination of the π 2 ‐type levels. This leads to a conformation where Ag is located in one face along the symmetric C 3 ‐axis (Figures and ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition to silver, Sn(II) is another representative ion in the formation of cation−π complexes, as seen from the chemistry of [2.2.2]paracyclophane ([2.2.2]pCp) acting as suitable polyaromatic receptor for metal cations involving three aromatic rings . A notorious difference between the characterized complexes of Ag(I) and Sn(II) with [2.2.2]pCp, is given by the location of the cation denoting an η 2 : η 2 : η 2 coordination mode for the former, and a contrasting η 6 : η 6 : η 6 fashion for Sn(II) involving a richer bonding scheme owing to the ligand→5p‐Sn shell charge donation, which encourage us to evaluate their plausible incorporation in the helicene chemistry ,…”
Section: Introductionmentioning
confidence: 99%